Expedition and Characterization of the Corpse Flower (Amorphophallus titanum (Becc.)) in West Sumatra - Yusniwati, Yusniwati; Setiawan, Ryan Budi; Handayani, Mellyyana; Nanda, Alifma Rahimmi; Sukma, Dian; Rahmi, Alfazlul; Syahputra, Agil; Bosma, Pandu Arif Laksana; Baiturrahman, Atzim (Jurnal Manajemen Hutan Tropika, 2024)
The corpse flower (Amorphophallus titanum Becc.) is an endemic flora of Indonesia that is naturally found only in Sumatra. The status of A. titanum is endangered because of several factors: deforestation, tuber exploitation, long flowering time, and protogyne. Until now, there has been no research about the population and distribution of A. titanum in West Sumatra. This study aimed to obtain information about the population and distribution of A. titanum in West Sumatra, so this research is essential to learn. The research used roaming and snowball sampling methods in Solok Selatan and Sijunjung Regencies in September-October 2022. The research was conducted by recording the coordinates where A. titanum was discovered, marked using GPS, and collecting morphological characteristics. The results showed that exploration in the Solok Selatan District found 19 corpse flower individuals (18 species of A. titanum and one species of A. gigas). In contrast, exploration in Sijunjung Regency managed to found 25 species of A. titanum. The corpse flowers found were in vegetative, dormant, flowering, and fruiting phases. The results help record the number and distribution of A.titanum in West Sumatra. The ex-situ conservation program will use germplasm as propagation material in the future.